Active Cycle Breathing Technique on Airway Clearance in Pulmonary TB Patients - Pomalango, Zulkifli B; Suleman, Ibrahim (Jambura Nursing Journal, 2024)
Abstract Introduction: Gorontalo City has 643 cases of tuberculosis in 2022, with the problem of ineffective airway clearance which causes airway obstruction which is often characterized by symptoms of ineffective cough, excess sputum, wheezing and rhonchi. Objective: To determine the effect of active cycle breathing technique on airway clearance in pulmonary TB patients. Method: The type of research used is quantitative. The research design uses a Quasi Experiment One Group Pre test- Post test design, namely a research design that only uses one group of subjects and takes measurements before and after giving treatment to the subjects being studied. The sampling technique was carried out using the Accidental Sampling technique with a sample size of 10 respondents. Data analysis uses univariate and bivariate analysis and the instrument used is a questionnaire. Results: The results of the study showed that the patient's clinical results from ineffective airway clearance problems, after being given the active cycle breathing technique, resulted in effective airway clearance. The statistical test results obtained p-Value = 0.004, which means less than (Î± = 0.05), indicating that there is an influence of active cycle breathing technique on airway clearance in pulmonary TB patients. Conclusion: The active cycle breathing technique can be a recommended nursing intervention in overcoming the problem of airway clearance in pulmonary TB patients.